Exploring ESL learners’ blended learning experiences and its’ effectiveness through web-based technologies - Sangeeth Ramalingam; Melor Md Yunus; Harwati Hashim (Institute of Advanced Engineering and Science, 2021)
The inability to gain employment among the Malaysian graduates became a critical issue due to lack of 21st century skills. Higher learning institutions are urged to play their significant roles in producing graduates who have subject knowledge and relevant 21st century skills. There are many teaching strategies which are currently in practice at tertiary institutions, however more efficient approach is needed to produce well-balanced graduates. This present research proposed a promising approach which is blended learning with web-based technologies to improve students’ 21st century skills. Current literature indicated blended learning has not been sufficiently explored in English as Second Language (ESL) context. Thus, this study aimed to explore ESL learners’ blended learning experiences using innovative web-based technologies and to examine the effectiveness of the blended learning strategy in improving the learners’ 21st-century skills. Qualitative data were collected through phone call interviews with the participants and analyzed through thematic analysis. Working with a sample of bachelor degree students at a tertiary institution revealed the participants’ blended learning experience exceptionally improved their 21st-century skills in various ways. The result of this study contributes to the pedagogical aspects of ESL teaching and learning and the improvement of 21st century skills among the students.